Produção e qualidade de serapilheira e aporte de nutrientes emsistemas agroflorestais de agricultores familiares do norte de MinasGerais - Anna Crystina Alvarenga (2012)
The aim of this study was to evaluate the sustainability of three Agroforestry Systems located in the Agroextrativista Americana Settlement, the city of Grão Mogol - MG, based on the quantification of litter deposition, the potential contribution of nutrients to the soil, in the structural quality of the litter and in the chemical soil properties along the fourth seasons. It was considered two groups depending on the soil class, being one in Oxisol (AFS 1, AFS 2 and native vegetation 1) and another in Gleysoil (AFS 3 and native vegetation 2). For the evaluation of the litter were installed 20 collectors 1m ² on each system. The intercepted material was collected at the end of the seasons to estimate the production and composition of litter produced. For the evaluation of the soil chemical attributes were collected composite samples for each treatment, at 0-5 and 0-20 cm depth in each season. The management of Agroforestry Systems influences the contribution and the composition of the litter. Regarding areas of adjacent native vegetation, the litter deposited by AFSs has higher concentrations of components easily degradable that favor nutrient cycling. The amount of nutrients deposited through litter are sufficient to supply the nutritional needs of most cultures present in the Agroforestry Systems studied, besides maintain and, or improve the soil chemical attributes and maintenance of the soil organic matter.